INVESTIGATING LINGUISTIC CHALLENGES ARISING FROM TRANSLATING PROVERBS FROM ENGLISH INTO ANOTHER LANGUAGE - Inog’omjonova Robiya Rustamjon qizi; Rustamov Ilkhom Tursunovich (Journal Park Publishing, 2024)
Proverbs and sayings are deeply rooted in the culture and history of a specific nation and making easy to understand for those from other cultures. Some scholars argue that these linguistic expressions cannot be effectively translated, while others propose various translation techniques to address this challenge. This article examines this issue in detail, using comparative, contrastive, and content analyses. To test differing perspectives, some English proverbs were randomly selected and translated into Uzbek.
Keywords: equivalence, methods, tools, phraseological units, translation, idiomatic expression.